Evaluación de la motilidad y viabilidad del semen bovino a distintas temperaturas de descongelación y a diferentes intervalos de tiempo post- descongelación - Villavicencio Celi, Pablo Andrés (2025)
Cryopreserved semen is a key tool for success in reproductive biotechnologies, due to its ability to preserve sperm functionality for long periods, proving to be effective in mitigating the adverse effects of cryopreservation by improving post-thawing sperm survival. This study aimed to evaluate bovine semen thawed at different temperatures and its viability in the postthawing time. 18 straws from the GENEX commercial company were used, the semen that was analyzed belongs to the NICODEMUS – ET bull of the Holstein breed. The straw was removed and evaluated in a water bath at 38°C and 40°C and kept for 30, 60, and 90 minutes; then they were evaluated on a slide on the thermal plate in the Androscope equipment, 5 layers of each sample were taken and the CASA program provided a report for each straw. When individual motility and minimum motility of 30% were evaluated at two temperatures of 38° and 40°, in scales of 30, 60, and 90 minutes for each straw, there was no statistical difference, so postthawing at the two temperatures does not influence semen quality. In addition, when evaluating temperature, minimum time, and total motility, there was no statistical difference, however, with a temperature of 38° C and a longer time (90 minutes) the motility is greater, on the contrary, at temperatures of 38° C and a medium time (60 minutes) the motility is reduced by half. The motility and viability of semen post-thawing are not affected at temperatures of 38°C and 40°C, so the quality of the semen remains intact over time.